2009
DOI: 10.1016/j.molcel.2009.04.014
|View full text |Cite
|
Sign up to set email alerts
|

HMGN Proteins Act in Opposition to ATP-Dependent Chromatin Remodeling Factors to Restrict Nucleosome Mobility

Abstract: SUMMARY The high mobility group N (HMGN) proteins are abundant nonhistone chromosomal proteins that bind specifically to nucleosomes at two high affinity sites. Here we report that purified recombinant human HMGN1 (HMG14) and HMGN2 (HMG17) potently repress ATP-dependent chromatin remodeling by four different molecular motor proteins. In contrast, mutant HMGN proteins with double Ser to Glu mutations in their nucleosome-binding domains are unable to inhibit chromatin remodeling. The HMGN-mediated repression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
78
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(81 citation statements)
references
References 43 publications
3
78
0
Order By: Relevance
“…Indeed, nucleosomes bound to either full-length HMGN2 (26) or the NBD (13) are more resistant to thermal denaturation than when in the free state. The staple feature of the NBD suggests that HMGNs may act in opposition to ATP-dependent chromatin remodeling factors by restricting the motion of the DNA in the nucleosome or sterically blocking remodeling factors from binding to the nucleosome (10). Steric interference by HMGNs may also affect the ability of histone modifiers to access and modify their nucleosomal targets (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, nucleosomes bound to either full-length HMGN2 (26) or the NBD (13) are more resistant to thermal denaturation than when in the free state. The staple feature of the NBD suggests that HMGNs may act in opposition to ATP-dependent chromatin remodeling factors by restricting the motion of the DNA in the nucleosome or sterically blocking remodeling factors from binding to the nucleosome (10). Steric interference by HMGNs may also affect the ability of histone modifiers to access and modify their nucleosomal targets (11).…”
Section: Discussionmentioning
confidence: 99%
“…HMGNs decompact chromatin condensed by the linker histone H1 (8), thereby enhancing transcription activity of the chromatin template. In addition, HMGNs affect DNA repair (9), chromatin remodeling (10), and the extent of histone modifications (11).…”
mentioning
confidence: 99%
“…In the nucleus, HMGN proteins serve as a counterbalance to the action of the many ATP-dependent chromatin remodeling activities which are involved in the formation of actin filaments in the cytoplasm. 5,36) Therefore, we speculated that HMGN2 may be associated with actin filaments. In our studies, we also found that rHMGN2 decreased basal and K. pneumoniae 03183-induced cofilin phosphorylation and inhibited K. pneumoniae 03183-induced actin polymerization.…”
Section: Discussionmentioning
confidence: 99%
“…4) HMGN proteins serve as a counterbalance to the action of the many ATPdependent chromatin remodeling activities in the nucleus. 5) HMGN2 is a major regulator of homeodomain transcription factor activity modulated by Wnt/beta-catenin signaling. 6) Recently, an additional role for HMGN2 outside the cell nucleus has come into focus.…”
mentioning
confidence: 99%
“…The binding of HMGNs to nucleosomes affects chromatin-related processes such as transcription, replication, and repair (2,4,5,16,20,27,41,43). HMGNs may mediate these effects by causing a change in chromatin structure (5,27) or the level of histone posttranslational modifications (22,23), by affecting ATP-dependent chromatin remodeling activities (30), or by a combination of these.…”
mentioning
confidence: 99%